Chemical Migration from Plastic Bottled-water Containers under Environmental Stress: A Critical Review of Toxicological Mechanisms, Ecological Effects and Clinical Health Implications - S. Shoba; M. Hemashri; K. Jalakandeswari; K. Jeeva; I. Rukshana; D. Uvasri (Journal of International Research in Medical and Pharmaceutical Sciences, 2026)
Plastic bottled water is a complex exposure system in which the bottle body, closure, processing history, water chemistry and post-production environment can all influence the transfer of chemicals and particles into the contained water. This critical narrative review evaluates evidence on migration from polyethylene terephthalate (PET) bottles and relevant closure or reusable-bottle polymers under thermal, photochemical, temporal and mechanical stress, and integrates that evidence with toxicological, ecological and clinical-health literature. Literature published from 1 January 2000 to 22 June 2026 was examined using multidisciplinary scholarly sources, citation searching and authoritative drinking-water guidance. The most reproducible stress-dependent signal in PET systems is increased antimony migration with rising temperature and contact time, although concentrations vary substantially by bottle composition, water matrix and experimental conditions. Carbonyls, PET-related degradation products and other non-intentionally added substances also show condition-dependent migration. Reports of phthalates, bisphenols and estrogenic activity require more cautious source attribution because these compounds are not necessarily intrinsic to the PET polymer and may arise from closures, recycled feedstock, processing, environmental contamination or other package components. Mechanical opening and closing can generate particles at the cap-neck interface, while modern nano-analytical methods detect far more small particles than earlier microscopy-based studies, making cross-study concentration comparisons highly method-dependent. Mechanistic evidence supports oxidative stress, inflammation, endocrine signalling and organelle disturbance for selected chemicals or micro- and nanoplastics, but these findings are dominated by in vitro and animal models and often use doses that are difficult to map onto ordinary bottled-water intake. Human biomonitoring confirms internal exposure to plastic particles from multiple environmental pathways, yet no clinical study establishes bottled water as a causal source of human disease. Ecological evidence indicates that weathered plastic can release biologically active chemical mixtures, but toxicity is strongly polymer- and additive-dependent. Risk assessment should therefore distinguish chemical migration from particle release, identify the true material source, model realistic stress histories, and avoid translating hazard signals directly into clinical risk.